Crystal Structure and Cyclic Voltammetric Studies on the Metal Complexes of N-(Dimethylcarbamothioyl)-4-fluorobenzamide - Gun Binzet; Ersan Turunc; Ulrich Flörke; Nevzat Külcü; Hakan Arslan (Journal of Chemistry)
We synthesized N-(dimethylcarbamothioyl)-4-fluorobenzamide compound and its copper(II) and nickel(II) complexes. The structures of compounds have been characterized by elemental analysis and spectral data (IR, 1H NMR). Furthermore, crystal and molecular structure of the synthesized complexes have been identified by using single crystal X-ray diffraction data. In the complexes formation the metal atom was coordinated via two sulfur atoms and two oxygen atoms. The single crystal structure of copper(II) and nickel(II) complex exhibits slightly distorted square planar geometry. The oxygen atoms are in a cis configuration. It appeared that the lengths of the thiocarbonyl and carbonyl bonds are longer than the average for C=S and C=O; meanwhile the C‐N bonds in the complex ring appeared to be shorter than the average for C‐N single bonds. These data show that C-O, C-S, and C-N bond lengths of the complexes suggest considerable electronic delocalization in the chelate ring. All bond lengths and angles obtained as a result of the analyses are found to be within experimental error limits. The obtained crystal analysis data shows that the structure of complex compounds is compatible with similar compounds in literature. Electrochemical behavior of complexes has been investigated by cyclic voltammetry technique in aprotic media. From the cyclic voltammetric investigation, both of the complexes have demonstrated electroactive properties.